HPB P02 Audit of Delays in the Definitive Management of Suspected Pancreatic Malignancies. (7th December 2022) - Fyfe, Jadé; Singhal, Natasha; Walker, Alexander; Sprackling, Isabel; Aroori, Somaiah
Abstract: Background: Approximately 10, 500 people in the UK are diagnosed with pancreatic cancer each year. (1) Patients can present to their GP, to A&E, or can be referred following an incidental finding on a pathology review. Decisions within the South-West of England regarding patient's most appropriate treatment pathways are made during Specialist Multi-Disciplinary Team (SMDT) meetings hosted by University Hospitals Plymouth (UHP). Treatment options can include surgery, chemotherapy or a palliative approach. (2) The NHS standard for patients to have their first definitive treatment following an urgent GP referral is a maximum of 62 days. (3) Shorter waiting times have been shown to correlate to an improved patient experience, and may result in earlier diagnoses, treatment, fewer complications, and overall improved cancer outcomes. (4) This audit aims to review the current practice of the time taken between the date of referral and the first definitive treatment of pancreatic malignancies discussed within the SMDT over a two-year period. Currently, there are no studies examining the relationship between delays and patient outcomes with pancreatic malignancies in England. (5) Our evaluation will also examine this and enable future planning into research studies with a particular focus on reducing delays in treatment. Methods: A retrospective, cohort study across the South-West of England analysing the delays in the definitive management of suspected pancreatic malignancies within a two-year period of weekly SMDT discussions. The inclusion criteria consists of patients referred locally from Plymouth Hospitals NHS Trust with pancreatic and peri-ampullary malignancies, discussed between 01/01/19 and 31/12/20. A total of 94 patients were discussed within the SMDT with suspected pancreatic and peri-ampullary cancers in 2019. 61 of these patients were referred locally from Plymouth Hospitals NHS Trust and will be the focus for this abstract. Following approval from the hospitals ethics board, data has been retrospectively collected by our team of four medical students into the online RedCap database. (6) Data has been collected from following hospital systems: Somerset Cancer Register, Clinical Record Interactive System, e-discharge and patient care manager and the main hospital electronic system. Data collection points include patient age, date of initial presentation, dates and types of investigations, date of SMDT referral, number and outcome of SMDT discussions, date of treatment commencement, and date of death if applicable. The data has been anonymised to explore the sources of delay from the date of referral until definitive treatment in patients with pancreatic malignancies. Results: The age range for our preliminary data is 50–91. The median age is 71. Preliminary data shows that overall: For patients surgically managed, it took a median of 0 days from their first presentation until their date of surgery (range 189), with longer delays for those referred form their GP compared to those referred via admission. For patients managed with chemotherapy, it took a median of 81 days from their date of first presentation until their date of first chemotherapy treatment (range 231).For patients treated palliatively, it took a median of 23 days from their date of first presentation to the date of decision for palliative treatment (range 77). The number of SMDT discussions per patient had a range of 7, with a median of 2. On further analysis, delays lie between: The date of first presentation to SMDT referral, especially if referred via GP (median 9, range 17) compared to via admission (median 0, range 72) The date of SMDT referral and date of first discussion (median 9, range 53) The date of first SMDT discussion and date of first biopsy (median 31, range 165) Conclusions: Preliminary data analysis shows that patients are waiting longer than nationally stipulated NHS guidelines. Upon complete data analysis of all patients first discussed within the SMDT in 2019 and 2020, an evaluation of the timeframe and delays to receiving definite management will highlight the adherence to the NHS 62-day target and whether this has improved over time. We will consider the impact of recurring SMDT discussions on patient outcomes. We will identify any trends between the time taken from being first seen until definitive treatment and analyse the impact of these on the mortality of our patient cohort. Could this be contributing to the poor survival of pancreatic malignancies in England compared to the rest of Europe? (7) On completion, analysis will enable identification of the factors contributing to any delays in the existing treatment pathway in the South-West of the England. We will suggest future means of addressing these to improve this timeframe in accordance with NHS targets, with the goal to potentially improve patient outcomes. References 1. https://www.cancerresearchuk.org/about-cancer/pancreatic-cancer/about 2. https://www.plymouthhospitals.nhs.uk/liver-hpb-pathways 3. https://www.england.nhs.uk/wpcontent/uploads/2015/12/planning-guid-16-17-20-21.pdf 4. https://www.england.nhs.uk/statistics/wpcontent/uploads/sites/2/2020/02/Cancer-Waiting-Times-Quarterly-CommentaryProvider-based-Provisional-1.pdf 5. https://www.researchgate.net/publication/327886931_The_Multidisciplinary_Team_MDT_in_Cancer_Services_Improving_Efficiency_in_Line_with_Increasing_Workload 6. https://www.project-redcap.org/ 7. https://www.cancerresearchuk.org/health-professional/cancer-statistics/statistics-by-cancer-type/pancreatic-cancer/survival#heading-Three